Discovery of an endogenous Deltaretrovirus in the genome of long-fingered bats (Chiroptera: Miniopteridae) - Farkašová, Helena; Hron, Tomáš; Pačes, Jan; Hulva, Pavel; Benda, Petr; Gifford, Robert James; Elleder, Daniel (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Retroviruses can create endogenous forms on infiltration into the germline cells of their hosts. These forms are then vertically transmitted and can be considered as genetic fossils of ancient viruses. All retrovirus genera, with the exception of deltaretroviruses, have had their representation identified in the host genome as a virus fossil record. Here we describe an endogenous Deltaretrovirus, identified in the germline of long-fingered bats (Miniopteridae). A single, heavily deleted copy of this retrovirus has been found in the genome of miniopterid species, but not in the genomes of the phylogenetically closest bat families, Vespertilionidae and Cistugonidae. Therefore, the endogenization occurred in a time interval between 20 and 45 million years ago. This discovery closes the last major gap in the retroviral fossil record and provides important insights into the history of deltaretroviruses in mammals.
Keywords: sekvence nukleotidů; Nucleic Acid Conformation; endogenní retroviry; Chiroptera; Consensus Sequence; fylogeneze; Phylogeny; Deltaretroviruses; molekulární evoluce; Evolution, Molecular; Genomics; Deltaretrovirus; Endogenous Retroviruses; genom; konformace nukleové kyseliny; Animals; otevřené čtecí rámce; konsenzuální sekvence; zvířata; Open Reading Frames; endogenous retroviruses; Base Sequence; Genome; virové geny; Genes, Viral; genomika